2006
DOI: 10.1007/s11418-006-0003-0
|View full text |Cite
|
Sign up to set email alerts
|

A new iridoid glucoside from the Thai medicinal plant, Morinda elliptica Ridl

Abstract: A new plumieride type iridoid glucoside, morinipticoside, was isolated from the leaves and branches of Morinda elliptica together with six known compounds; asperuloside, asperulosidic acid, yopaaoside A, yopaaoside B, benzyl a-L-arabinopyranosyl (1 fi 6)-b-D-glucopyranoside and phenyethyl a-L-arabinopyranosyl(1 fi 6)-b-D-glucopyranoside. The structure determinations were based on physical data and spectroscopic evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…However, there are a few reports on the presence of other types of compounds, particularly anthraquinones [6] and triterpenoids [7,8]. As part of our further continuing studies on Rubiaceous plants [9][10][11][12][13], we investigated the chemical constituents of this plant collected from Thailand. This paper describes the isolation and identification of ten polar constituents, including eight iridoid glucosides (1)(2)(3)(4)(5)(6)(7)(8) The dried whole plants of O. corymbosa (1.7 kg) were macerated with MeOH.…”
mentioning
confidence: 99%
“…However, there are a few reports on the presence of other types of compounds, particularly anthraquinones [6] and triterpenoids [7,8]. As part of our further continuing studies on Rubiaceous plants [9][10][11][12][13], we investigated the chemical constituents of this plant collected from Thailand. This paper describes the isolation and identification of ten polar constituents, including eight iridoid glucosides (1)(2)(3)(4)(5)(6)(7)(8) The dried whole plants of O. corymbosa (1.7 kg) were macerated with MeOH.…”
mentioning
confidence: 99%
“…The Rubiaceae family is known for the production of alkaloids, iridoids, and anthraquinones (YOUNG et al, 1996), and flavonoids have been isolated from species of this family (LOPES et al, 2004, CARDOSO et al, 2005PINTO et al, 2008). Noiarsa et al (2006) identified 18 substances from the aerial parts of Spermacoce laevis Roxb. including flavonoids and iridoids, the latter being designated as a chemotaxonomic marker for species of the Rubeaceae family.…”
Section: Resultsmentioning
confidence: 99%
“…The remaining compounds were identified as asperulosidic acid (2), 12 daphylloside (3), 13 asperuloside (4), 13 (1R, 6R,9R) 6,9,11-trihydroxy-4-megastigmen-3-one (7), 4-epiborreriagenin (8), 14 trans-phytol (9), 15 ursolic acid lactone (10), 17 3β-hydroxyurs-12-en-28-al (11), and ursolic acid (12) 16 (see Figure 1). Their structures were established on the basis of spectral and chemical evidence, which were in good agreement with those reported in literature.…”
Section: Notesmentioning
confidence: 99%